Inactivated tetanus as an immunological smokescreen: A major step towards harnessing tetanus-based therapeutics. (November 2020) - McLean, Thomas; Norbury, Luke; Conduit, Russell; Shepherd, Natalie; Coloe, Peter; Sasse, Anthony; Smooker, Peter
Highlights: Tetanus toxin has great therapeutic potential, matching botulinum toxin. Widespread vaccination has hindered such development. A strategy to circumvent immunity has been developed. This allows the use of localised toxin application at reduced doses in vaccinated animals. Abstract: Background and purpose: Tetanus neurotoxin has many potential therapeutic applications, due to its ability to increase localised muscle tone when injected directly into a muscle. It is a closely related molecule to botulinum neurotoxin (most commonly known as Botox), which has been widely used to release muscle tension for therapeutic and cosmetic applications. However, tetanus toxin has been relegated to the "maybe pile" for protein therapeutics — as most of the population is vaccinated, leading to highly effective antibody-mediated protection against the toxin. The potential for tetanus-based therapeutics remains substantial if the problem of pre-existing immunity can be resolved. Experimental approach: A well-established murine model of localised muscular contraction was utilised. We administered functional tetanus toxin combined with an immunogenic, but functionally inactive, decoy molecule. Key results: Incorporation of the decoy molecule greatly reduces the dose of active toxin required to induce a localised increase in muscle tone in mice vaccinated with the human toxoid vaccine. Conclusion and implications: Our results clearly demonstrate that the barriers to developing a tetanus toxin therapeutic are not insurmountable and the technology presented here is the first major step towards realising the therapeutic potential of this powerful neurotoxin. Opening the therapeutic potential of tetanus toxin will have huge implications for the wide range of diseases caused by low-tone muscle.